From dusk till dawn: cell cycle progression in the red seaweed Gracilariopsis chorda (Rhodophyta) - JunMo Lee; Shin-ya Miyagishima; Debashish Bhattacharya; Hwan Su Yoon (iScience, 2024)
Summary: The conserved eukaryotic functions of cell cycle genes have primarily been studied using animal/plant models and unicellular algae. Cell cycle progression and its regulatory components in red (Rhodophyta) seaweeds are poorly understood. We analyzed diurnal gene expression data to investigate the cell cycle in the red seaweed Gracilariopsis chorda. We identified cell cycle progression and transitions in G. chorda which are induced by interactions of key regulators such as E2F/DP, RBR, cyclin-dependent kinases, and cyclins from dusk to dawn. However, several typical CDK inhibitor proteins are absent in red seaweeds. Interestingly, the G1-S transition in G. chorda is controlled by delayed transcription of GINS subunit 3. We propose that the delayed S phase entry in this seaweed may have evolved to minimize DNA damage (e.g., due to UV radiation) during replication. Our results provide important insights into cell cycle-associated physiology and its molecular mechanisms in red seaweeds.